The Reform of Intergovernmental Fiscal Relations in Developing and Emerging Market Economies - Shah, Anwar (Washington; World Bank, 1994)
An important dimension of public sector reform in developing and emerging market economies has been the loosening of central control over the private sector and lower level governments. The author's overview of the principles and best practices of fiscal federalism should help guide policy debates on restructuring intergovernmental fiscal arrangements. Strong emphasis on central planning impedes innovative responses to local issues by local governments and stymies private sector development. Decentralization should be the rule, the author argues, unless a strong case can be made for centralizing specific responsibilities. Local public services can be provided more efficiently if expenditures more closely match local needs and preferences. More closely linking benefits to costs also promotes accountability. Increased fiscal autonomy can also help mobilize more revenue from local sources, improving a country's fiscal position. And decentralized desicion-making encourages local participation in development. Constitutional responsibilities should be stated clearly and precisely. Tax and spending assignments should be determined simultaneously, so revenue means are matched as closely as possible to spending needs at each level of government. In most developing countries, subnational governments have limited access to their own tax bases and depend on higher level transfers. A grant's design should reflect the situation and objectives. The author gives examples. Although most countries give a high priority to limiting interregional fiscal disparities, no developing or transitional economy has adopted an explicit standard for equalization. Revenue sharing should be supplemented by an equilization program with a specified standard rather than by combining several factors into one formula. Local borrowing to meet capital expenditures is a major issue in most developing countries. In such cases, autonomous bodies can supervise and assist local borrowing for capital projects. The decentralization of responsibilities and the rationalization of intergovernmental transfers should be supported by strengthening local institutional capabilities. Monitoring, auditing, and inspections functions in most developing nations especially need to be strengthened. Transitional economies also need to give high priority to establishing or improving framework laws on property rights, corporate legal ownership and control, and bankruptcy, and financial accounting and control
Includes Reference
Keywords: Developing countries; BUSINESS & ECONOMICS Public Finance; Intergovernmental fiscal relations Developing countries